Real world macro - Fireside, Daniel; Synder, Bryan; Miller, John.; Dollars & Sense Collective; Dollars & Sense (Boston, MA Dollars and Sense, 2008)
Covers macroeconomic basics: monetary and fiscal policy; productivity and investment; inflation and unemployment. Includes chapter on major controversies in macroeconomics.
Measuring economic performance -- Wealth, inequality, and poverty -- Savings and investment -- Fiscal policy, deficits, and debt -- Monetary policy and financial markets -- Unemployment and inflation -- Perspectives on macroeconomic policy -- International trade and finance.
Gift from American University, Dept. of Economics.
Keywords: Macroeconomics; Economics -- Government policy; United States -- Economic conditions -- 2001-.